(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
In this study, an artificial neural network was formed to estimate the load- deflection curve behavior of simply supported beams with polymer reinforcement. Available actual (experimental) values for several beams from previous studies were used to construct a neural network model. The results obtained from this network were compared with the actual values ​​and with the specifications of the American Code ACI 440.1 R and it was found that the values ​​obtained from the neural network are very close to the laboratory values ​​and present more accurate results ​​than the values ​​obtained from the equations of the American Code, where the neural results were more compatible with the actual study curves with a greater degree compared to what the American code equations estimated.